Transarterial therapy combined with bevacizumab plus immune checkpoint inhibitors as a neoadjuvant therapy for locally advanced HCC - Yang, Zhenyun; Wang, Qianyu; Hu, Li; Sima, Xiaoxian; Wang, Juncheng; Hu, Dandan; Zhou, Zhongguo; Chen, Minshan; Zhang, Yaojun; Fu, Yizhen (Frontiers in Immunology, 2024)
BackgroundTransarterial therapy (TAT), bevacizumab (Bev), and immune checkpoint inhibitors (ICIs) have individually exhibited efficacy in treating advanced-stage hepatocellular carcinoma (HCC). This study aimed to assess the efficacy and safety of the combination of these three treatments as a neoadjuvant modality in patients with locally advanced HCC.MethodsThe primary endpoint is overall survival (OS). The second endpoint is progression free survival (PFS), objective response rate (ORR), pathological response rate and safety.ResultsA total of 54 patients received standard systemic therapy comprising Bev combined with ICIs (Bev-ICIs group), 113 patients received direct surgery (Surgery group), and 273 patients received neoadjuvant therapy of TAT combined Bev plus ICIs, among which 79 patients (28.9%) underwent surgical resection after successful tumor downstaging (Neo-surgery group) while the remaining 194 patients (71.1%) received maintenance systemic therapies (Neo-maintenance group). Neoadjuvant following surgery demonstrated a prolonged OS in contrast to direct surgery, with a median OS time not reached in the Neo-surgery group and 30.6 (95% CI: 26.4-34.7) months in the Surgery group (hazard ratio (HR)=0.29, P=0.0058). The median PFS time in the Neo-surgery and Surgery groups stood at 19.2 (95% CI: 16.1-22.2) and 6.3 (95% CI:4.7-8) months, respectively (HR=0.25, P<0.0001). In patients failed to receiving resection after neoadjuvant therapy, the median OS was 22.8 (95% CI: 22.3-23.1) months, whereas that for the standard care population was 19.7 (95% CI: 15.9-24) month (HR=0.53, P=0.023). The median PFS time in Neo-maintenance group and Bev-ICIs groups was 11.2 (95% CI: 10.4-11.9) and 6.4 (95% CI: 4.4-8.5) months (HR=0.60, P=0.024). The ORR and disease control rate (DCR) across all patients received TAT-Bev-ICIs were 38.8% and 89.4%, respectively. Additionally, the pathological complete response (pCR) rate and the major pathological response (MPR) rate were 22.8% and 48.1% in the Neo-surgery group. As for safety, neoadjuvant therapy did not increase the perioperative complications when compared to direct surgery, and demonstrated similar incidences and severity of AEs when compared to the standard systemic therapy.ConclusionThe triple therapy regimen comprising TAT-Bev-ICIs emerged as a promising therapeutic strategy for locally advanced hepatocellular carcinoma (HCC) as a neoadjuvant intervention.